Implementasi Kurikulum Merdeka Pada Mata Pelajaran Seni Tari Kelas VIII SMPN 5 Padang - Fitri Anggia; Marzam Marzam (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This study aims to determine and describe the implementation of the Independent Curriculum in Class VIII Dance subjects of SMPN 5 Padang. This type of research is qualitative, with a descriptive approach. The researcher's own research instruments and assisted by supporting instruments such as stationery, cameres, and mobile phones. Data collection techniques are carried out through literature studies, observations, interviews, and documentation. Data analysis techniques are collecting data, classifying data, analyzing data, describing data and inferring data. The results showed that the implementation of dance learning at SMPN 5 Padang was carried out well, but there were several things in the implementation of learning where the implementation did not use teaching modules. During learning, the teacher also does not motivate students and does not conclude the learning that has been carried out every day. Teachers have used methods that are in accordance with the learning material, although many students have not maximized in practicing dance creations on the material in semester 2.